Complex use of perfusion techniques in kidney transplantation from a donor with out-of-hospital cardiac arrest (clinical case) - A. V. Shabunin; M. G. Minina; P. A. Drozdov; I. A. Miloserdov; D. A. Saydulaev; V. M. Sevostyanov; E. A. Tenchurina (Вестник трансплантологии и искусственных органов)
Objective: to present the successful experience with a donor with out-of-hospital cardiac arrest (OHCA) in whom a set of modern perfusion techniques was used to obtain kidneys suitable for transplantation.Materials and methods. Automatic chest compression was resumed in an OHCA donor (after biological death has been confirmed in the hospital) to maintain minimal perfusion under mechanical ventilation with 100% FiO2. With femoral vein cannulation, an extracorporeal circuit with a centrifuge pump and oxygenator was connected and abdominal normothermic regional perfusion was initiated. After 215 minutes, kidney was explanted under normothermic machine perfusion. Next, the left kidney was placed in the LifePort Kidney Transporter for hypothermic machine perfusion of donor kidneys. Perfusion time was 285 minutes. The right kidney was transplanted without additional ex-vivo perfusion.Results. Due to the complex use of perfusion techniques both in the donor body and ex-vivo, donor kidneys, after OHCA, with a total warm ischemia time of 110 minutes, were transplanted to recipients with good results. In the postoperative period, there was delayed function of the left and right renal grafts. The patients were discharged in a satisfactory condition under outpatient follow-up.Conclusion. The possibility and efficiency of organ donation after OHCA, facilitated by modern perfusion techniques and devices, open up a new perspective in addressing the organ shortage crisis.